The relationship between athletes’ grit, mental toughness, and sport resilience - Bengie Mendizabal (Physical Education of Students)
Background and Study Aim. Several studies have been conducted on athletes’ grit, mental toughness, and sports resilience. However, such studies have not been documented for athletes in the Higher Education sector in the Philippines. Therefore, this study aimed to determine the relationship between grit, mental toughness, and sports resilience among student-athletes at a selected state university.